The role of thrombin and protease-activated receptors in pain mechanisms - García, Paul S.; Gulati, Amitabh; Levy, Jerrold H. (Thrombosis and Haemostasis, 2010)
As our knowledge of the mechanisms underlying the sensation of pain continues to expand, researchers are constantly searching for novel therapeutic targets. One such novel pain pathway involves thrombin and its associated protease-activated receptor (PAR). Besides its traditional role in haemostasis, thrombin has multiple roles in both the central and peripheral nervous system including activation of microglia, regulation of neuronal death and neurite outgrowth, and influencing the transmission of pain signals in the nociceptive circuitry. Eventually therapeutic modalities directed at these targets could provide novel therapeutic approaches for treating chronic pain. The thrombin-associ-ated PARs also have roles in inflammation, neurodevelopment, and conducting pain, both in conjunction with thrombin and independently. Recent laboratory evidence suggests that the PARs can attenuate pain mediated by the enteric nervous system in animal models (for example in pancreatitis and colitis). This review highlights several pathways in the mediation of pain sensation that can be influenced by thrombin.
Keywords: Thrombin; protease activated receptor; pain; hemostasis; coagulation; inflammation